2016
DOI: 10.5296/jet.v4i1.10422
|View full text |Cite
|
Sign up to set email alerts
|

Consultation in Special Needs Education in Rural Schools in Sweden– An Act of Collaboration between Educators

Abstract: The article attempts to shed light on how the expertise of special educators can be utilized in classroom teachers' professional development at rural schools with a diverse student body. The study focused on the educational consultations that took place between the two types of professionals, namely the special educators and the classroom teachers, at three rural schools in three communities in northern Sweden. The special educators did not work at the schools. Rather, they worked at Community centers and ran … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
(66 reference statements)
0
9
0
1
Order By: Relevance
“…The relatively few studies that examined special educational consultations offered some examples of cooperation in which power and responsibilities were equally shared (e.g. Eisenman et al 2011;Pettersson and Ström 2017). Challenges found in studies focusing on interprofessional cooperation with a consultative character, on the other hand, were associated, for instance, with a lack of communication between the cooperating actors (Bray and Russell 2018;Hemmingsson, Gustavsson, and Townsend 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The relatively few studies that examined special educational consultations offered some examples of cooperation in which power and responsibilities were equally shared (e.g. Eisenman et al 2011;Pettersson and Ström 2017). Challenges found in studies focusing on interprofessional cooperation with a consultative character, on the other hand, were associated, for instance, with a lack of communication between the cooperating actors (Bray and Russell 2018;Hemmingsson, Gustavsson, and Townsend 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Four studies described and analysed special educational consultations. Different models of consultations were reported that could be classified, using Sundqvist's (2012) categorisation, as both reflective conversations (Kjaer and Dannesboe 2019) and cooperative conversations (Pettersson and Ström 2017). Kjaer and Dannesboe (2019) describe consultations between educational psychologists and regular teachers as having a therapeutic character, where teachers were supposed to search within themselves for alternative instructional approaches, attitudes and behaviours.…”
Section: Special Educational Consultationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pettersson, Ström & Johansen 2016;Pettersson 2017). Tidigare svenska studier (Pettersson, Ström & Johansen 2016;Pettersson & Ström 2017;Pettersson & Näsström 2017) har dock utarbetat följande definition: glesbygdsskolan är belägen i olika geografiska områden i fjälltrakter, i inland, på öar och i kustregioner. Glesbygdsskolan har få lärare och få elever (55 elever eller färre).…”
unclassified